Programma: 21 januari - 1 februari; 25 januari The Fabulous Poodles; 29 januari Flo & Eddie, 31 januari Braak; 1 februari The Spiderz (1981)
Programma: 21 januari - 1 februari; 25 januari The Fabulous Poodles; 29 januari Flo & Eddie, 31 januari Braak; 1 februari The Spiderz.